Introduction to mutation and disease - Wolfe, Jonathan (Henry Stewart Talks, 2009)
Types of mutation, Point mutation, Submicroscopic deletion or insertion, Microscopically visible deletion, translocation or inversion, Loss of a whole chromosome, Dominance or recessivity, Dominant negative mutations in collagen genes, Retinoblastoma, Williams Syndrome, Fragile X, Trinucleotide expansion mutations